Aged care residents in the emergency department: the experiences of relatives. Issue 23 (12th August 2015) - Morphet, Julia; Decker, Kelly; Crawford, Kimberley; Innes, Kelli; Williams, Allison Fiona; Griffiths, Debra
Abstract : Aims and objectives: The aim of this study was to investigate the experiences of relatives who had a family member in an aged care facility subsequently transferred to an emergency department. Background: The provision of timely and relevant patient information is vital for assessment and management of older patients presenting to the emergency department from aged care facilities. Older people are commonly accompanied by relatives who are an important resource for emergency department staff, providing medical information and assisting with treatment decisions. Investigating the experiences of relatives may provide key information to enable improvements in the delivery of emergency department care. Design: This study used a descriptive qualitative design. Methods: Semi‐structured interviews were undertaken with 24 relatives of residents who were transferred from an aged care facility to an emergency department in Victoria, Australia in the previous three years. Inductive content analysis was used to analyse the transcripts. Results: Relatives reflected on four main themes following their emergency department visit: The need for clear communication; The role of relatives in emergency department care; How older people are perceived in the health care system and an Ability to provide specialised care. Conclusions: Many people link their emergency department experience to the quality of communication with emergency department staff, and participants in this study felt satisfied with their visit when they were included in discussions about treatment, and their role was recognised by staff members. In contrast, participants were dissatisfied with the care provided to their family member when staff members failed to communicate with them, or recognise their role in the care of the family member. Relevance to clinical practice: The findings of this study emphasise the importance of effective communication between emergency department staff and family members, in relation to treatment and end‐of‐life care.